2023
DOI: 10.1186/s40104-022-00803-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate, calcium, and vitamin D signaling, transport, and metabolism in the endometria of cyclic ewes

Abstract: Background Recent evidence suggests important roles for progesterone (P4) and interferon tau in the regulation of calcium, phosphate, and vitamin D signaling in the uteri of pregnant sheep. However, the effects of P4 and estradiol (E2), with respect to the expression of their receptors PGR and ESR1, respectively, in uterine epithelia on mineral signaling during the estrous cycle has not been investigated. Estrous cycles of mature Suffolk ewes were synchronized, prostaglandin F2α was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Stages in which expression was examined are: (1) Day 1 (early metestrus) characterized by decreasing concentrations of E2 and low concentrations of P4 in maternal plasma, and expression of both ESR1 and PGR in uterine epithelia; (2) Day 9 (early diestrus) characterized by low concentrations of E2 and high concentrations of P4 in maternal plasma with the downregulation of ESR1 and upregulation of PGR in uterine epithelia; and (3) Day 14 (late diestrus) characterized by very low concentrations of E2, high concentrations of P4 in maternal plasma, and the decreased expression of both ESR1 and PGR in uterine epithelial cells [27–29]. Results of this study revealed no effect of Day of the estrous cycle on expression of ALPL mRNA which is consistent with a lack of an effect of Day of the estrous cycle on the abundance of phosphate in uterine f lushings in sheep [3234]. However, there tended to be lower endometrial expression of ALPL mRNA on Day 9, suggesting that increasing concentrations of P4 in plasma, which can bind to PGR in uterine LE and sGE, is associated with decreased endometrial expression of ALPL mRNA.…”
Section: Discussionsupporting
confidence: 80%
“…Stages in which expression was examined are: (1) Day 1 (early metestrus) characterized by decreasing concentrations of E2 and low concentrations of P4 in maternal plasma, and expression of both ESR1 and PGR in uterine epithelia; (2) Day 9 (early diestrus) characterized by low concentrations of E2 and high concentrations of P4 in maternal plasma with the downregulation of ESR1 and upregulation of PGR in uterine epithelia; and (3) Day 14 (late diestrus) characterized by very low concentrations of E2, high concentrations of P4 in maternal plasma, and the decreased expression of both ESR1 and PGR in uterine epithelial cells [27–29]. Results of this study revealed no effect of Day of the estrous cycle on expression of ALPL mRNA which is consistent with a lack of an effect of Day of the estrous cycle on the abundance of phosphate in uterine f lushings in sheep [3234]. However, there tended to be lower endometrial expression of ALPL mRNA on Day 9, suggesting that increasing concentrations of P4 in plasma, which can bind to PGR in uterine LE and sGE, is associated with decreased endometrial expression of ALPL mRNA.…”
Section: Discussionsupporting
confidence: 80%
“…On Day 12 of gestation, endometria from P4 treated ewes had greater expression of ALPL mRNA, which was accompanied by an apparent increase in TNSALP activity in epithelia, stratum compactum stroma, and endothelial cells of blood vessels in the endometrium and myometrium. We have recently reported greater TNSALP activity in the endometrial stratum compactum stroma of Day 14 cycle ewes compared to that for endometria from Day 1 or Day 9 of the estrous cycle [ 32 ]. Thus, it could be speculated that following PGR downregulation in the endometrial LE and sGE, P4 not only alters TNSALP to alter phosphate availability in epithelia, but also regulates TNSALP activity in the endometrial stratum compactum stroma, which could alter phosphate availability.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of reference genes was assessed by geNORM V3.5 (Ghent University Hospital, Centre for Medical Genetics, Ghent, Belgium) with an M value of < 1.5. The reference genes tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (% YWHAZ ) and beta-2-microglobulin ( B2M ) were determined to have stable expression across days of the estrous cycle [18]. Additionally, effects of day of the estrous cycle were determined using JMP to ensure that there was no effect of day on the expression of the reference genes ( P> 0.1).…”
Section: Methodsmentioning
confidence: 99%